GAMBARAN PENGETAHUAN DAN PENANGANAN PERAWAT SEBAGAI FIRST RESPONDER PADA KEJADIAN IN HOSPITAL CARDIAC ARREST (IHCA) - Arlies Zenitha Victoria; Felicia Riska Ryandini; Fransiska Apriliyana Wati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Backgorund : In Hospital Cardiac Arrest (IHCA) is a cardiac arrest event that occurs in a hospital. Handling is fast in less than 5 minutes after the event of cardiac arrest and knowledge of nurses as first responders and the correct way of handling can help patients obtain a Return of Spontaneous Circulation (ROSC). Objective :This study aims to describe the knowledge overview and the nurses handling as first responders in the incidence of in-hospital cardiac arrest (IHCA). Methods : The research used retrospective descriptive methode. Data retrieval by analized the code blue team documents in January 2022 with the criteria of nurses being the first responders of patients experienced by cardiac arrest, questionnaire sheet used and interviews with nurses first responders on the incidence of cardiac arrest in January 2022 (84 respondents) Results : The result was the majority of respondents aged 26-35 years as many as 39 respondents (46.4%), mostly female 78 respondents (92.9%), with Diploma education 51 respondents (60.7%) and Professional nurses 33 respondents (39.3%) and 43 respondents (51.2%) had good knowledge, 38 respondents (45.2%) had sufficient knowledge and the handling of cardiac arrest was good as many as 66 respondents (78.5%). A total of 54 respondents (64.3%) have joined BLS & BTCLS training and 30 respondents (35.7%) have joined BLS, BTCLS & ACLS training. Conclusion : The conclusion of this study was the nurses have good knowledge and methods of handling IHCA patients.